2004
DOI: 10.1111/j.1365-2990.2003.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective PrP‐like protein, doppel immunoreactivity in dystrophic neurites of senile plaques in Alzheimer's disease

Abstract: Doppel (Dpl) is a prion-like protein encoded by the gene PRND, which has been found downstream of the prion gene PRNP in several species. The present study examines by immunohistochemistry Dpl expression in brain samples from 10 patients with Alzheimer's disease (AD), three patients with Pick's disease, four patients with Parkinson's disease, eight patients with diffuse Lewy body disease (DLBD), six patients with sporadic Creutzfeldt-Jakob disease (CJD) methionine/methionine at the codon 129, two patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In addition, the up-regulation of astrocyte-specific genes in PrP-deficient mice ectopically expressing Dpl, has suggested that Dpl is actively involved in glial cell activation in the brain (46). Recently, however, Ferrer and collaborators described a Dpl accumulation in abnormal neurites of senile plaques, probably originated from impaired transport and subcellular localization or by an anomalous turnover of the protein (20). Similarly, tumor astrocytes exhibited a Dpl accumulation within the cells, that seems associated with the WHO astrocytoma malignancy grades (Chiarelli and Valentini, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the up-regulation of astrocyte-specific genes in PrP-deficient mice ectopically expressing Dpl, has suggested that Dpl is actively involved in glial cell activation in the brain (46). Recently, however, Ferrer and collaborators described a Dpl accumulation in abnormal neurites of senile plaques, probably originated from impaired transport and subcellular localization or by an anomalous turnover of the protein (20). Similarly, tumor astrocytes exhibited a Dpl accumulation within the cells, that seems associated with the WHO astrocytoma malignancy grades (Chiarelli and Valentini, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the expression of the doppel gene has been investigated in other pathological contexts. Ferrer and collaborators (20) have recently reported a selective Dpl immunoreactivity in dystrophic neuritis in Alzheimer's disease patients. In tumors, the first evidence of a possible implication of Dpl has been recently produced by our group, reporting an aberrant PRND expression in the astrocytic and leukaemic specimens with different malignancy grades (21,22).…”
Section: Introductionmentioning
confidence: 98%
“…However, opposite to AD, in sCJD increased levels of BACE1 activity in CSF did not correlate with higher levels of BACE1 protein in brain. Since amyloid plaques have been detected in sCJD brain patients [49][51], these results suggest a disturbed Aβ metabolism in sCJD [42], [52], [53].…”
Section: Discussionmentioning
confidence: 73%
“…The relationship between the PrPC and physiopathological mechanisms of Alzheimer's disease (AD) is well understood [23][24][25][26][27][28][29]. On our part, we have observed a particular behaviour of PrPC in brains with AD.…”
Section: Introductionmentioning
confidence: 68%